LCD backlights. - Kobayashi, Shunsuke, ....-; Lim, Sungkyoo, ....-; Mikoshiba, Shigeo, ....- (Chichester : Wiley, 2009)
Part I: Backlights by use: Technical trends and requirements/specifications for LCD TV backlights -- Improvement of moving picture quality by means of backlight control -- Multiple primary color backlights -- Reduction of backlight power consumption of LCD-TVs -- Notebook PC/monitor backlights -- Backlights for handheld data terminals -- Part II: Light source devices: CCFL backlights -- CCFL inverters -- HCFL backlights -- EEFL backlights -- FFL backlights -- Magnetically coupled electrodeless lamps -- Mercury-free fluorescent lamp backlights -- LED backlights -- Technological trends of LED backlight units -- White OLED backlights -- Inorganic EL backlights -- Field emission backlights -- Part III: Optical components: Light-guide plates -- Optical diffuser plates -- Lens films and reflective polarization films.
Keywords: LCD (Liquid Crystal Displays).